Effect of cannabinoid receptor ligands on microglial cell functions - Hassan, Samia (2013)
Background: Microglial cells can be regarded as the macrophages of the central nervous system. Their activation has protective functions in the destruction of pathogens, removal of debris and release of neurotrophic factors, but excessive activation can exacerbate the effects of inflammation contributing to neurodegenerative conditions such as Alzheimers disease. The cannabinoids have a variety of anti-inflammatory properties and the main aim of this project is to determine the role of cannabinoids in modulation of microglial cell function using in vitro approaches, and to investigate the molecular mechanisms underlying such modulation. Methods: BV-2 murine microglial and primary murine microglial cells were activated using bacterial lipopolysaccharide (LPS). Nitric oxide (NO) was determined with a Griess assay. Western blotting was used to measure the expression of NFκB p65, Ikβα, inducible nitric oxide synthase (iNOS), COX-2, and total and phosphorylated forms of the MAP kinases, p38, JNK1/2 and ERK1/2; blots were analysed with an Odyssey imaging system (Li-Cor Bioscience), Expression of GPR55 mRNA was determined by RT-PCR. Phagocytosis was assessed in BV-2, HAPI and primary murine microglial cells and in RAW 264.7 monocyte/macrophages using fluorescent latex beads and the cells viewed by confocal microscopy. Fluorescent bead accumulation was quantified on consecutive image and rate phagocytic was calculated by normalizing the number of beads to the number of cells in each field. Western blotting was used to measure the expression of the receptor channels TRPV2 and TRPV1 and AKT. Immunocytochemistry was used to investigate the translocation of TRPV2, and the involvement of MLC11, PLCγ2, PKCα, ε in phagocytosis. Fura-2-based Ca2+ imaging of microglia was undertaken and migration was assessed using a novel “Compass” device. Result: BV-2 cells did not express CB1 or CB2 receptor mRNA; however, the cannabinoid receptor agonist CP55-940, the CB1 antagonist AM251and the non-psychoactive cannabinoid cannabidiol (CBD) all at 10μM produced significant inhibitions of lipopolysaccharide (LPS; 100ng/ml)-stimulated nitric oxide (NO) formation. The putative GPR55 receptor agonists VSN16R and O1916 (were without effect, as was the endogenous GPR55 agonist lysophosphatidylinositol (LPI). A number of other cannabinoid receptor agonists and antagonists and the phytocannabinoids (CBG, CBDV, THCV, CBDA and CBGA (Pertwee, 2008) (all 10 µM) were without. Cannabidiol inhibited LPS-enhancement of both iNOS and COX-2 expression. LPS significantly induced phosphorylation of the MAP kinases ERK 1/2, p38 and JNK and CBD inhibited both LPS-induced p38 and JNK phosphorylation but was without effect on phosphorylation of ERK1/2. The p38 inhibitor SB203580 (10 µM) also significantly reduced iNOS expression after 24 hours of LPS stimulation. LPS increased NF-KB p65 expression and this was significantly attenuated by CBD. LPS also stimulated NF-KB p65 translocation to the nucleus whereas CBD inhibited the effect. CBD-induced phagocytosis of BSA latex beads was similarly induced in HAPI, RAW264.7 and primary murine microglial cells. Inhibitors of Rho kinase (Y27632) and PI (3)kinase (wortmannin) inhibited basal but not CBD-enhanced phagocytosis. CBD increased intracellular calcium in BV-2 cells and the TRP channel blocker ruthenium red reversed CBD-induced phagocytosis. CBD increased expression of TRPV2 protein and mRNA and caused a translocation to the cell membrane. This was abolished in presence of cycloheximide and PI3K inhibitor. Other cannabinoids and phytocannabinoids (CBG, CBDV, THCV, CBDA and CBGA) were without effect. CBD also increased BV-2 cell migration. Conclusion: The data presented demonstrate that CBD, despite inhibiting NO formation, mediated by reduction of NF-kβ P38 MAPK, JNK and ROS activity, enhances microglial migration and phagocytosis. The mechanism of action appears to involve TRPV2 channel activation accompanied by increased protein synthesis and translocation to the cell membrane. Therefore, CBD might be developed as a useful treatment for neurodegenerative disease.